Effect of sustainability accounting and reporting on financial performance of firms in PT pertamina Persero - Ceisari, Btari Bunga (Enrichment : Journal of Management, 2024)
Conventional financial report has been criticized for only representing operational-related matters but not including and explaining multiple dimensions of the corporation’s value. The above-mentioned gives rise to the idea of sustainable reporting where it reflects the company’s effort and concern about environment protection and inter-generation equality. The research aims to identify the significant relationship between sustainability reporting represented by the environment, social, and government (ESG); and firm’s performance in Indonesian Firms (Pertamina). The data is taken from Pertamina sustainability reporting and official websites. As a state-owned company, Pertamina should provide more consistent and clear information on its sustainability investments and expenses. It should be reflected in its annual report and sustainability report. The research type that will be used in this study is quantitative research. The research object is one of the Indonesian state-owned companies, namely PT Pertamina Persero. This study analyses The Annual Financial Statement and Sustainability Reporting of PT Pertamina Persero Indonesia in 2013-2020 as the research object. The period has been chosen because PT Pertamina started to use GRI Index (G4) started from the year of 2013. Variable used in this research are Sustainability Report Disclosure Index (SRDI), expenses, and investment contributes to the company’s sustainability effort as independent variables. Dependent variables consist of financial ratios, such as liquidity, profitability, and solvency ratios. Finally, this study concludes that there is a positive relationship between investment for sustainability and SRDI, between sustainability investment and firm performance, between the company’s sustainability expenses with ROE, and between SRDI and financial ratios of PT Pertamina Persero.